Analisis Jalur Infrastruktur Jalan terhadap Pembangunan Ekonomi Sumatera Barat: Peran Keuangan Daerah sebagai Variabel Mediasi - Muhammad Satria Aldi; Zulkifli N (Badan Penelitian and Pengembangan (Balitbang), Padang, West Sumatra, Indonesia, 2026)
This study examines the effect of road infrastructure on regional economic development in West Sumatra Province, with a focus on the mechanism through which this effect is mediated by regional finance. Empirical data were collected from 19 regencies and municipalities observed over the period from 2019 to 2023. A mediation model was applied in the analysis. The analysis utilized Partial Least Squares Structural Equation Modeling (PLS-SEM) using SmartPLS 4.0 software. The results indicate that road infrastructure does not have a direct effect on economic development in West Sumatra Province. In this relationship, regional finance acts as a full mediator in transmitting the indirect effect of road infrastructure on economic development, with a coefficient of 0.396. These findings indicate that, to make road infrastructure a catalyst for equitable economic development across regions, strong regional fiscal capacity should be a primary focus of government policy, considering the potential for more effective absorption of regional investments into the economic potential of each regency/municipality in West Sumatra Province. The findings also recommend integrating road infrastructure development with appropriate fiscal strategies to achieve sustainable regional economic development.